The Crisis of the COVID-19 Pandemic and the Expansion of E-Learning in Egypt - Tera, Maryam Shawky Abdelrahman; Rabie, Amira Ahmed (Journal of Educational and Psychological Sciences, 2020)
The current research aims to present the various dimensions of the Covid 19 virus pandemic and its effects, learn about e-learning and the needs of digital transformation, and identify the Egyptian government’s direction in containing the Covid 19 pandemic crisis. And identifying the teachers’ skills for using e-learning tools and employing them in education. And to identify the extent of schools’ readiness to expand in e-learning, and to identify the most important needs of rapid digital transformation in education, and to achieve the goal of the study, the descriptive approach was used, where a questionnaire consisting of four areas was prepared with (34) paragraphs, and after making sure of its validity and consistency, it was distributed to The study sample consisting of (130) teachers and teachers, the results of the study showed that the arithmetic averages of the responses of the sample members about the degree of teachers ’possession of skills for using e-learning tools and their use in education were low. The results of the research also indicated that there are no statistically significant differences between the responses of the sample members about the degree to which teachers possess the skills of using e-learning tools and employing them in education according to the variables (years of experience - academic qualification). The study concluded that the Ministry of Education should hold training courses for teachers and equip them with the skills to deal with digital age technology and its educational applications. And also the necessity of providing digital devices for teachers on the sites and applications that the teacher needs, as the base for delivering tablets to basic education teachers such as secondary teachers in the new system must be expanded and applications that facilitate the teacher’s work on them must be provided. And the need to provide digital devices for teachers on the sites and applications that the teacher needs, as the base for handing tablet devices to primary education teachers such as secondary teachers in the new system must be expanded and applications that facilitate the teacher’s work on them must be provided. Also, the need to provide a strong Internet for learners to allow them to self-learn during the pandemic period.